### Show Posts

This section allows you to view all posts made by this member. Note that you can only see posts made in areas you currently have access to.

### Topics - AllanLi

Pages: [1]
1
##### Quiz-4 / quiz 4 tut 0401
« on: October 18, 2019, 02:29:22 PM »
find the general solution to the given equation

9y''+6y'+y=0
we get

9r^2+6r+1=0
solve for r, we have

3r+1=0, r = -1/3
so we have

y(t) = C1e^{-1/3}+C2te^{-1/3}

2
##### Quiz-3 / quiz 3 tut 0401
« on: October 11, 2019, 02:02:30 PM »

y'' + 3y' = 0 , y(0) = -2, y'(0) = 3
we get

r^2 + 3r = 0
Solve for r, we get the solution for r.

r1= -3, r2 = -3
For the repeated roots, the solution for y is

y(t) = C1e^{rt} + C2te^{rt}
So we have

y(t) = C1e^{-3t}+tC2e^{-3t}
Since

y(0) = -2, y'(0) = 3
We will have two equations about C1 and C2

C1 = -2, -3C1 + C2(1+0) = 3
So we have

C1 = -2, C2 = -3
Then the solution is

y(t) = -2e^{-3t}-3te^{-3t}

y(t) = - (2+3t)e^{-3t}

3
##### Quiz-2 / quiz 2 tut 0401
« on: October 04, 2019, 02:00:02 PM »

(2xy^2+2y)+(2x^2y+2x)y'=0
write y' into dy/dx, then we get

(2xy^2+2y)dx+(2x^2y+2x)dy=0
Let M = 2xy^2+2y , N = 2x^2y+2x , we get

\frac{dM}{dy}= 4xy + 2 , \frac{dN}{dx} = 4xy + 2
Since dM/dy = dN/dx, therefore they are exact. So ∃ 𝛗(x,y) = ∫ M dx

𝛗(x,y) = ∫ M dx = ∫ 2xy^2 + 2y dx = x^2y^2 + 2xy + h(y)
d𝛗(x,y)/dy = N

4x^2y + 2x +h'(y) = 2x^2y + 2x
we get h'(y) = 0 => h(y) = C, C is a constant.At the end we got the answer

𝛗(x,y) = x^2y^2 + 2xy +C

Pages: [1]